THE CONCEPT OF SHARIA TOURISM IN REGULATION OF LAW NO. 33 OF 2014 ABOUT HALAL PRODUCT GUARANTEE - Dini Nurul Hidayah; Fanny Nurrusyifa (STIESA Press, 2020)
Indonesia as a country with a majority Muslim population has a wealth of traditions and customs that cannot be separated from its religion. Tradition and culture in society today are manifestations of their religion and beliefs. So that now it can no longer be separated between customs or culture and religion, both of them have merged into one unit, namely tradition in Indonesian society. Based on that, this paper aims to explain that halal products that are on halal tourism have been regulated in law no. 33 of 2014. In this case Law Number 33 of 2014 concerning Halal Product Guarantee regulates one of the rights and obligations of Business Actors by providing exceptions to Business Actors who produce products from ingredients that are prohibited by the obligation to state explicitly information not halal on product packaging or on certain parts of the product that are easily seen, read, not easily erased, and are an inseparable part of the Product.29 In addition, to ensure law enforcement against violations of this law, administrative sanctions and criminal sanctions.